THE RELATIONSHIP BETWEEN INCIDENCE OF RESPIRATORY DISTRESS SYNDROME AND INCREASING OF TROPONIN T LEVELS IN PREMATURE NEONATES AT NEONATOLOGY WARD ADAM MALIK GENERAL HOSPITAL - Annisa Zuhrah, Supriatmo, Emil Azlin & Rita Evalina Rusli (International Journal of Research Science and Management, 2020)
Respiratory distress syndrome is a major cause of morbidity in low birth weight infants (LBW). Troponin T is a marker of myocardial damage in premature neonates with asphyxia where high troponin T levels found in premature neonates with respiratory distress syndrome. A Cross-sectional study was conducted in neonatology ward, H. Adam Malik hospital, Medan from November 2017 to April 2018. The inclusion criteria was premature neonates in gestasional age < 36 weeks with respiratory distress syndrome. The data collected were analyzed using Chi Square test. P value < 0,05 was considered significant. Of participants 35, 30 meets the criteria. There were 23 premature neonates with respiratory distress syndrome (76,7%) and 7 premature neonates without respiratory distress syndrome (23,3%). Troponin T increases in premature neonates with respiratory distress syndrome. There were relationship between increasing troponin T level and incidence of respiratory distress syndrome in premature neonates.